DEPARTMENT OF TRADITIONAL MEDICINE, THONG NHAT HOSPITAL - Thiên Vũ, Phan; Văn Đàn, Nguyễn; Thị Nhã Trúc, Lê; Thị Hạnh, Lê; Thị Lan Hương, Lê; Thành Lộc, Trần; Thị Hồng Diễm, Võ; Thái Hiền Trang, Nguyễn (Journal of Health and Aging, 2025)
The rate of insomnia is increasing in today’s life, finding effective non-pharmacological treatments for insomnia is very necessary. Intravascular low-level laser therapy is a new method in the treatment of insomnia disorders that needs to be exploited and evaluated for its therapeutic effectiveness when combined with manual acupuncture in Traditional Medicine. Determine the efficacy of low-level laser therapy combined with acupuncture versus acupuncture alone in the treatment of non-organic insomnia. Sixty patients diagnosed with non-organic insomnia at the Department of Traditional Medicine, Thong Nhat Hospital, from February 2024 to July 2024. The patients were randomly divided into two groups. The intervention group (n=30) received treatment with low-level laser therapy combined with manual acupuncture, while the control group (n=30) received manual acupuncture. The efficacy of the treatment was evaluated based on the Pittsburgh Sleep Quality Index (PSQI) and the number of awakenings before treatment, as well as at 5 and 10 days after treatment. After 10 days of treatment, the group receiving manual acupuncture combined with low-level laser therapy showed a significant and notable reduction in PSQI scores compared to the group receiving only manual acupuncture. The PSQI score decreased from 17.2 to 13.33, a total reduction of 3.87 points, reflecting a change in sleep disturbance from moderate to mild. The average sleep onset time reduced from 101.67 minutes to 41 minutes, corresponding to a decrease in the score from 2.63 to 1.43. The average number of hours of sleep per night increased from 3.23 hours to 5.27 hours, with a score reduction from 2.9 to 2.1. The average sleep efficiency improved from 40.59% to 59.91%, with a score decrease from 2.87 to 2.5. In terms of sleep quality, the score decreased from 2.9 to 1.87. The average daytime dysfunction score reduced from 1.77 to 1.1, and the number of awakenings decreased from 2.70 to 1.77. These improvements were statistically significant compared to the group receiving only manual acupuncture. The combined method of manual acupuncture with low-level laser therapy is more effective than manual acupuncture in the treatment of non-organic insomnia.
Keywords: Non-organic insomnia; Manual acupuncture; Low-level laser therapy